Surgical Planning for the Treatment of a Patient with Multiple, Secondary, Intracranial Echinococcal Cysts - Chatzidakis, Emmanouel; Zogopoulos, Panagiotis; Paleologos, Theofilos S.; Papageorgiou, Nikolaos (The Surgery Journal, 2016)
A 27-year-old man with a 2-year history of recurrent hospitalizations for various neurologic and cardiologic emergencies was admitted to our hospital presenting with left hemiparesis, which gradually progressed to quadriparesis, bilateral hemianopsia, intracranial hypertension syndrome, and seizures. A diagnosis of echinococcosis was made, based on the radiologic findings of multiple cerebral hydatid cysts and a sizable cyst of the heart. The hydatid cyst of the heart was treated first with a thoracotomy, and after a month he underwent three consecutive surgical operations for the removal of six cerebral cysts. The patient was on albendazole treatment throughout the entire hospitalization, and this led to the shrinkage and finally to the disappearance of two other cerebral cysts. The patient's focal neurologic signs eventually disappeared, with the exception of a slight unilateral hemianopsia. Ten years after his discharge, he remains in a good condition, with no signs of clinical or radiologic relapse.
Keywords: hydatid cyst; cerebral cyst; echinococcosis; surgical treatment; surgical planning